Causality matters in medical imaging - Daniel C. Castro (Nature Portfolio, 2020)
Scarcity of high-quality annotated data and mismatch between the development dataset and the target environment are two of the main challenges in developing predictive tools from medical imaging. In this Perspective, the authors show how causal reasoning can shed new light on these challenges.